CHARACTERISTICS OF CHANGING A COMPLAINT OFFENSE INTO A REGULAR OFFENSE IN THE CRIMINAL ACT OF MARITAL RAPE - Nikita Rafa Sahara; Erny Herlin Setyorini (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study examines the urgency of changing the complaint-based offense into a regular offense in rape crime within marriage as regulated in Article 473 paragraph (6) of the National Criminal Code. Although Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS) views sexual violence as a serious issue, there is legal disharmony because the National Criminal Code and Article 52 of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT) still categorizes rape by a husband against his wife as a complaint-based offense. Using normative legal research methods with a statutory and legal conceptual approach, this study analyzes the philosophical, sociological, and juridical foundations of these regulations. Sociologically, economic dependence, social pressure, and patriarchal culture often hinder victims from reporting. Philosophically, the state has a constitutional responsibility to protect the human rights and sense of security of every citizen without exception. The study concludes that the definition of "violence" in Articles 89 and 90 of the Criminal Code, such as unconsciousness or serious injury, should be the basis for changing the status of a case to an ordinary crime. The author recommends that law enforcement officials process reports from third parties based on Article 108 of the Criminal Procedure Code to ensure justice for victims and eliminate impunity for perpetrators in the domestic sphere